The Influence of Entrepreneurial Ecosystem on Entrepreneurial Perceptions and Entrepreneurial Success - Faizah, Niswatul; Effendi, Mohammad Irhas; Ghofar, Abdul (Universitas Muhammadiyah Yogyakarta, 2024)
Research aims: This research aims to determine the impact of entrepreneurial ecosystems on entrepreneurial perceptions and entrepreneurial success.Design/Methodology/Approach: The sample in this research was 118 bamboo handicraft MSMEs (Micro, Small Medium Enterprise) in Sleman Regency Yogyakarta, selected using the cluster random sampling method with data data analysis using SEM-PLS.Research findings: The results of this study showed that entrepreneurial ecosystem variables such as market access, human resources, government regulations, and infrastructure had a significant positive impact on entrepreneurial success and entrepreneurial perceptions. However, education and training, as well as culture, do not Significantly influence.Theoretical Contribution/Originality: MSME performance is an important way to measure the success of MSMEs. A strong entrepreneurial ecosystem and positive perceptions of entrepreneurs are expected to improve MSME performance.Practitioners/Policy Implications: This research is expected to be a reference and consideration for SMEs and the government to strengthen entrepreneurial ecosystem factorso that it will have an impact on entrepreneurial perceptions and improve SME performance.Research Limitations/Implications: There are several limitations to this study that need to be considered for future research. First, the focus is only on certain industries, so caution is needed in generalizing the results to these industries. Second there were challenges in data collection due to unclear addresses and the closure of some MSMEs.